A deadlock-free routing algorithm using minimum number of virtual channels and application mappings for Hierarchical Torus Network - Rahman, M.M. Hafizur; Horiguchi, Susumu (Inderscience Publishers, 2006)
A Hierarchical Torus Network (HTN) is a 2D-torus network of multiple Basic Modules (BM), in which the BM are 3D-torus networks that are hierarchically interconnected for higher level networks. In this paper, we present a deadlock-free dimension-order routing using minimum number of Virtual Channels and evaluate the network's dynamic communication performance under the uniform traffic pattern by computer simulation and compare it with other contemporary conventional and hierarchical networks. We find that the dynamic communication performance of the HTN is better than that of the H3D-mesh, TESH, mesh, and torus networks. We also present the mapping of some primitive applications on the HTN. It is shown that the number of communication steps for various advanced applications mapping on the HTN is lower than that of those networks.